VA OpenNotes: exploring the experiences of early patient adopters with access to clinical notes. (28th October 2014) - Nazi, Kim M; Turvey, Carolyn L; Klein, Dawn M; Hogan, Timothy P; Woods, Susan S
Abstract: Objective To explore the experience of early patient adopters who accessed their clinical notes online using the Blue Button feature of the My Health e Vet portal. Methods A web-based survey of VA patient portal users from June 22 to September 15, 2013. Results 33.5% of respondents knew that clinical notes could be viewed, and nearly one in four (23.5%) said that they had viewed their notes at least once. The majority of VA Notes users agreed that accessing their notes will help them to do a better job of taking medications as prescribed (80.1%) and be better prepared for clinic visits (88.6%). Nine out of 10 users agreed that use of visit notes will help them understand their conditions better (91.8%), and better remember the plan for their care (91.9%). In contrast, 87% disagreed that VA Notes will make them worry more, and 88.4% disagreed that access to VA Notes will be more confusing than helpful. Users who had either contacted their provider or healthcare team (11.9%) or planned to (13.5%) primarily wanted to learn more about a health issue, medication, or test results (53.7%). Conclusions Initial assessment of the patient experience within the first 9 months of availability provides evidence that patients both value and benefit from online access to clinical notes. These findings are congruent with OpenNotes study findings on a broader scale. Additional outreach and education is needed to enhance patient awareness. Healthcare professionals should author notes keeping in mind the opportunity patient access presents for enhanced communication.